La France parmi nous: conscience historique et éducation européenne - Cristina Robalo Cordeiro (Carnets)
As a conclusion to a colloquium which brought together historians and literature teachers, it is probably necessary, in order to stress its interest, to denounce its problematic’s epistemological “ambivalence”. Are we talking about the same object when the discourse of literature and the discourse of history are mingling their words? We must remember that the former aims at putting the reader in a state of hysteria, leading him to live the events it recreates, while the latter, aspiring to be a scientific knowledge, wants to be objective, i.e. impassible. A European education should give its place to both, without mixing their teachings. This pedagogical task is our common duty.